2015
DOI: 10.1007/s00408-015-9766-y
|View full text |Cite
|
Sign up to set email alerts
|

Where is Noninvasive Ventilation Actually Delivered for Acute Respiratory Failure?

Abstract: Most NIV starts occurred in ICUs and EDs but utilization rate was highest (>50%) on general wards where a fifth of NIV starts took place. Actual location depended on etiology of ARF as patients with ACLD and APE were started more often in EDs and "de novo" ARF in ICU. NIV failure and mortality rates were higher in ICUs related to the greater proportion of patients with "de novo" ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
0
5
0
4
Order By: Relevance
“…Even in the USA, where NIV was almost exclusively used in ICUs in the 1990s, an observational cohort study based at eight acute care hospitals in Massachusetts found that, although only a fifth of acute NIV patients were started on general wards, the NIV utilisation rate was highest for general wards (73%), most likely reflecting the higher proportion of patients with a “do-not-intubate” status in general wards compared with critical care units [ 13 ].…”
Section: Summary and Prospectmentioning
confidence: 99%
“…Even in the USA, where NIV was almost exclusively used in ICUs in the 1990s, an observational cohort study based at eight acute care hospitals in Massachusetts found that, although only a fifth of acute NIV patients were started on general wards, the NIV utilisation rate was highest for general wards (73%), most likely reflecting the higher proportion of patients with a “do-not-intubate” status in general wards compared with critical care units [ 13 ].…”
Section: Summary and Prospectmentioning
confidence: 99%
“…O tempo médio da primeira sessão foi de 49,8 minutos (±30, 9), o número médio de sessões de VNI foi de 2,1 (±1,4) e o tempo total médio de realização de VNI foi de 110,2 minutos (±96,5 O tempo de sobrevida mediano global após a internação hospitalar foi de 25 dias (IC 95%: 0,00-71,12) para aqueles pacientes que apresentaram falha na VNI e 77 dias (IC 95%: 0,00-185,94) para os que obtiveram sucesso na VNI, e essa diferença foi estatisticamente significante (p=0,011) (Figura 1). O interesse no uso da VNI no cenário da UTI, enfermarias e emergência aumentou muito nos últimos anos 6,8,15,20,21 . Desde que não haja contraindicações, a VNI pode ser um tratamento de primeira linha para pacientes com câncer que apresentam IRA.…”
Section: Resultsunclassified
“…Desde que não haja contraindicações, a VNI pode ser um tratamento de primeira linha para pacientes com câncer que apresentam IRA. Uma das vantagens da utilização da VNI é a diminuição, ou mesmo a eliminação, da necessidade de intubação, consequentemente diminuindo as complicações associadas a esse método invasivo (trauma nas vias aéreas, infecções nosocomiais, necessidade de sedação) e diminuição dos custos hospitalares 22. A utilização da VNI para tratamento da IRA é mais alta na enfermaria quando comparada aos setores fechados de emergência e CTI 15 . Nas enfermarias, a segurança e o sucesso da VNI dependem de uma avaliação criteriosa dos pacientes, para distinguir aqueles que podem se beneficiar ou que apresentam riscos de falha.…”
Section: Resultsunclassified
See 2 more Smart Citations